Impact of Maqasid Al-Shariah for ethical decision making among social entrepreneurs - Mhd. Sarif, Suhaimi; Ismail, Yusof; Azan, Zaliza (2017)
Ethical decisions manifests the protection and preservation of benefits and rights of business stakeholders. The mainstream practice is based on conventional ethical principles. The use Maqasid al-Shariah is limited to Shariah compliant enterprises due to the industrial requirements or the need to gain competitive advantage. The unique model operations of social enterprises that combines for-profit and not-for-profit objectives has elements of Maqasid al-Shariah for ethical decision making. Based on personal interview with social entrepreneurs, the use of Maqasid al-Shariah is related to the wellness, welfare, and well-being of social enterprises and the key stakeholders. The results of the study suggest there is intermediate impact in terms of triple bottom line and stakeholders’ approach to ethical decision making of social entrepreneurs. The study suggests the use of case study method for future research.